Optimal synthesis of a community-based off-grid polygeneration plant using fuzzy mixed integer linear programming model - Ubando, Aristotle T. (Animo Repository, 2018)
Polygeneration provides an alternative approach for producing clean energy with enhanced overall thermodynamic efficiency, thus reducing environmental emissions and wastes. The growth of energy demand can be attributed to population growth together with the economic progress of developing countries. Such countries need to map out carbon-constrained growth trajectories that make intensive use of clean energy. In developing countries, there are still sites found in remote rural areas or islands which are still off-grid. Provision of electricity to such isolated communities is often problematic due to lack of economies of scale. Most of the livelihood of citizens in these areas is mainly based on agriculture and fisheries, which requires basic utilities such as electricity, clean drinking water, and cooling or refrigeration to preserve the agricultural produce and fishery catch. Polygeneration systems offer an efficient means of satisfying the utility needs of such remote communities. Hence, this study is focused on the development of a model for the optimal synthesis of community-based off-grid polygeneration plants needed to supply the basic needs of electricity, potable water, and cooling. The proposed approach uses a fuzzy mixed integer linear programming (FMILP) formulation. A hypothetical but realistic case study of a community-based off-grid is used to demonstrate the model. © 2018, AIDIC Servizi S.r.l.